Electron microscopy support

CN115362526BActive Publication Date: 2026-10-16UNITED KINGDOM RESEARCH AND INNOVATION
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202180024357.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-24
Filing Date
2021-03-24
Publication Date
2026-10-16
Estimated Expiration
2041-03-24

AI Technical Summary

Technical Problem

第一,在电子束辐照开始时的试样移动尤其降低图像品质并从结构中除去有关未受损分子的信息

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115362526B_ABST
    Figure CN115362526B_ABST
Patent Text Reader

Abstract

A support for an electron microscopy sample, the support comprising a metal foil having one or more holes therethrough, wherein the thickness of the metal foil is less than 50 nm and / or the average linear intercept grain size is 50 nm or less, wherein the ratio of the diameter of each hole to the thickness of the metal foil is 15:1 or less, and wherein the metal foil consists of: (a) one or more metals selected from transition metals, aluminum and beryllium, or alloys thereof; or (b) a degenerately doped silicon, wherein the dopant element is selected from boron, aluminum, boron and arsenic at a concentration of 10 20 atoms / cm 3 or more.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application claims priority to GB2004272.7, filed on March 24, 2020, the contents and elements of which are incorporated herein by reference for all purposes. Technical Field

[0002] This invention relates to electron microscopy (EM) sample supports; methods for manufacturing electron microscopy sample supports; methods for imaging using electron microscopy sample supports; and apparatus operable to perform the imaging methods. The supports are particularly useful in cryo-EM imaging. Background Technology

[0003] Electron microscopy is a technique used to image specimens. According to this technique, an electron beam is used to "illuminate" the specimen. The presence of the specimen in the electron beam causes a change in the beam. This change in the beam caused by the sample can be examined to produce a magnified image of the specimen.

[0004] In order to be irradiated by an electron beam, the specimen must be adequately supported within the beam. Typically, the electrons forming the electron beam have high energy, and it is understood that bombarding an object, such as the specimen used for examination, with the support holding the specimen in place within the electron beam, can cause physical, chemical, and / or electrical changes in the support and / or the specimen. Such changes can affect the results obtained using electron microscopy techniques (including image resolution).

[0005] In this regard, at least two problems remain unresolved in the field. First, sample movement at the onset of electron beam irradiation significantly degrades image quality and removes information about undamaged molecules from the structure. Consequently, all current EM structure determination models suffer from varying degrees of radiation damage. Second, the throughput of modern synchrotron crystallography beamlines far exceeds that of state-of-the-art electron microscopes, at least in part due to limitations in current EM sample supports. This means that while high-resolution structure determination via EM is feasible for drug discovery and development, the low throughput limits its practical application.

[0006] Ermantraut (1998) described carbon support foil for low-temperature EM. The aim was to minimize the total sample thickness to eliminate deformation of the object due to interaction with the support structure. The foil had square holes supporting ice layers as thin as 32 ± 2.3 nm. One carbon foil was described as 15 nm thick, and it is illustrated (but not shown) that it formed holes with diameters as small as 500 nm. This corresponds to a hole diameter to thickness ratio of 33.3:1.

[0007] Janbroers (2009) described a carbon-free, temperature-stable TEM grating. An 80% Au / 20% Pd metal film was supported on a standard hybrid Au TEM grating. The grating was formed by applying the metal to a carbon-covered TEM grating, followed by selective removal of the carbon using plasma cleaning. The circular apertures shown in the figures have diameters of approximately 1.5 μm or larger. The thickness of the 80% Au / 20% Pd metal film was set to 7 nm, 10 nm, or 15 nm. This corresponds to a minimum aperture diameter to thickness ratio of 100:1. The average grain size was 8.3 nm ± 2.0 nm, and the deposition occurred at room temperature.

[0008] Grant-Jacob (2016) described three-dimensional gold films with defined periodic geometries containing nanopores, designed to provide spatially localized enhancement of the electric field by manipulating plasmons within the nanopores. Because these films are not planar, they are unsuitable for suspending samples for analysis via electron microscopy. The substrate comprises an array of inverted pyramids etched into 4mm × 4mm square regions on the surface, with the inverted pyramids being 1.5μm × 1.5μm squares, 1μm deep, 2μm spaced, and 100nm thick. 50nm square nanopores were milled through the gold film at specific locations within the cavities to provide electric field control that can subsequently be used to enhance fluorescence or Raman scattering of molecules within the nanopores. This corresponds to a 2:1 ratio of pore diameter to thickness at the apex of the pyramidal structure. However, the pore walls were not thick enough to support the sample film. The average grain size was approximately 40nm, and deposition occurred at room temperature.

[0009] Jia 2019 describes large-area freestanding gold nanofilms with nanopores through the film having a thickness of 50 nm or greater. This corresponds to a pore diameter to thickness ratio of 5:1. However, gold nanofilms are formed by room temperature deposition, and therefore they do not provide the significant image quality improvement that is present in this invention.

[0010] Previous work by the inventors includes Russo 2014, which illustrates a gold sample support that virtually eliminates substrate movement during irradiation. The support therein has approximately Gold foil with square-patterned holes, 1.2 μm thick and 1.2 μm in diameter. This corresponds to a hole diameter to thickness ratio of 24:1.

[0011] Furthermore, in Russo 2016, an all-gold support was described, which has approximately to Gold foil with thickness and micrometer-diameter holes. This corresponds to a hole diameter to thickness ratio of at least 20:1.

[0012] All of the above-mentioned known gold support foils are at least Thick. This is because it is below approximately... Thick foils are currently unstable due to their polycrystalline grain structure, which typically has an average grain size of about 200 nm or larger. When forming foils smaller than approximately... When the foil is thick, it suffers from structural defects, such as gaps and cracks in the foil structure, which can lead to a lack of structural rigidity and thus sample movement, for example, during any thermal expansion caused by electron beam heating. Furthermore, the pores through such a film have significantly rough edges caused by individual grains, which is particularly noticeable at the edges of very small pores. This roughness negatively impacts the ease and stability of imaging. Moreover, thin gold foils with pore sizes smaller than 0.5 μm, optimized for single-particle cryogenic EM, cannot be produced using standard diffraction-limited lithography.

[0013] It is desirable to provide a support for electron microscopy, particularly for cryogenic EM, that addresses some of the problems of known specimen supports, such as undesirable movement during imaging. This disclosure was designed based on these considerations. Summary of the Invention

[0014] The inventors have discovered that undesirable movement during transmission electron microscopy imaging using current supports for electron microscopy is at least in part caused by tension buildup in the sample film, which can lead to film bending when the force exceeds a certain threshold. For example, tension accumulates in glassy ice films used to hold samples for cryogenic EM, where the bending threshold depends directly on the shape of the sample film. Taking cryogenic EM as an example, during cryoplunging to freeze aqueous samples, freezing at ≤10°C... -4 This occurs within a time interval of seconds. During this time, the change in water density is most rapid near the uniform nucleation temperature of 235 K. As the water solidifies, rapid cooling does not allow sufficient time for water molecules to rearrange their structure, resulting in the accumulation of compressive strain within the thin ice film. If the compression exceeds a critical value, the ice film bends, thus temporarily relieving the radial stress in the layer.

[0015] Bending only occurs when the stress exceeds a critical point, determined by the size of the ice film, its elastic modulus, its volume change relative to the support, and the constraint conditions at the aperture edges. As the glassy ice film continues to cool to the temperature of the surrounding refrigerant (typically liquid ethane at 90-93 K), further stress may accumulate due to further changes in relative density. Once the film has completely cooled to 77 K (liquid nitrogen temperature) and remains at 77 K, this stress is stored indefinitely within the film.

[0016] Even if the stress accumulated in the ice layer does not exceed the threshold that would cause the layer to bend, local heating may at least partially eliminate the retained stress when the sample is exposed to an electron beam in a transmission electron microscope (TEM), thereby causing the sample to move.

[0017] In short, the inventors discovered that the bending threshold of a membrane depends on its shape and size, which in turn are determined by the shape of the pores in which the membrane is suspended. The present invention is designed to minimize or avoid unwanted stress accumulation in the membrane, thereby reducing or completely eliminating sample movement, for example, caused by stress relief or bending during inspection. This significantly improves image quality.

[0018] In a first aspect, a support for electron microscopy samples is provided, the support comprising a metal foil having one or more holes therethrough, wherein the thickness of the metal foil is less than 50 nm and / or the average linear intercept grain size is 50 nm or less, wherein the ratio of the diameter of each hole to the thickness of the metal foil is 15:1 or less, and wherein the metal foil is composed of: (a) one or more metals selected from transition metals, aluminum and beryllium, or alloys thereof; or (b) degenerate-doped silicon, wherein the dopant element is selected from a concentration of 10 20 atoms / cm 3 Or higher levels of boron, aluminum, boron, and arsenic.

[0019] It is worth noting that any alternatives in the first aspect are corresponding technical features of these proposals, as they achieve the same technical effect of reducing sample movement to address the same technical problem of improving imaging.

[0020] Transition metals are elements in groups 3 to 11 of the periodic table.

[0021] In some cases, some or all of one or more transition metals are selected from one or more of precious metals (ruthenium, rhodium, palladium, silver, osmium, iridium, platinum, gold), copper, molybdenum, titanium, nickel, chromium, tungsten, hafnium, and tantalum, or alloys thereof. Preferably, one or more transition metals are selected from the precious metals ruthenium, rhodium, palladium, silver, osmium, iridium, platinum, gold, or alloys thereof. Preferably, one or more transition metals are selected from gold, palladium, and platinum or alloys thereof. Preferably, the metal foil contains gold or its alloys or is composed of gold or its alloys. Preferably, the alloy is a binary alloy. Particularly preferred alloys include gold-silver alloys, gold-copper alloys, nickel-titanium alloys, gold-platinum alloys, and platinum-iridium alloys. The foil may not contain aluminum. The foil may not contain beryllium. The foil may not contain alloys.

[0022] For the avoidance of doubt, the metal foil is not formed from electrical insulators, semiconductor materials, or carbon materials such as amorphous carbon or graphitic carbon, although these may exist in metal alloys as described herein. Semiconductor materials include materials whose conductivity decreases with decreasing temperature in the range of 300K to 80K. This includes carbon (amorphous or graphitic, but not diamond), silicon (below 10), and other materials. 20 / cm 3 (Doped with dopant elements such as boron, aluminum, phosphorus and arsenic), gallium arsenide and other III-V or II-VI binary semiconductors.

[0023] In some cases, the ratio of the diameter of each hole to the thickness of the foil is 11:1 or less, 10:1 or less, 8:1 or less, 7:1 or less, or 5:1 or less. The ratio of the diameter of each hole to the thickness of the foil can be 11:1 to 1:1, 10:1 to 2:1, 9:1 to 3:1, or 8:1 to 4:1.

[0024] The advantage of using a specified ratio is that it eliminates the curvature of such films when forming sample films in the holes, such as suspended amorphous ice films used in cryogenic EM. This allows for precise foil tracking during imaging with a high-speed detector, thereby reducing the requirements for the accuracy and stability of the cryogenic stage. Therefore, the support of the present invention reduces particle movement to a limit set by pseudo-diffusion, which is below the resolution of cryogenic electron microscopy. This allows for imaging at 300 keV... The amount of influence The complete image was reconstructed at high resolution. The sample film remained stable and under radial compression throughout the irradiation, with only diffusion movement occurring, confining it to [a specific location / condition]. Down The movement-suppressing microsurgical specimen support of the present invention allows for only The atomic structure was determined and extrapolated back to the point before the destructive effects of electron radiation affected the reconstruction.

[0025] In some cases, the metal foil is essentially free of structural defects. The absence of structural defects means that the foil material is essentially uniform and continuous. That is, there are no visible gaps or cracks in the foil, and the surface roughness is reduced. For example, based on the measured root mean square deviation relative to the expected theoretical aperture edge profile, the edge roughness of each aperture can be 20 nm or less, 15 nm or less, 10 nm or less, or 5 nm or less. The foil can have a roughness per 100 nm... 2 The area is only a single structural defect with a diameter of up to 1 nm.

[0026] The advantages of using metal foils with a thickness of less than 50 nm and without structural defects are that the foil is structurally stable and can be used to produce images with much higher resolution than previously possible using electron microscopy. Furthermore, the reduced foil thickness provides a thinner sample film in the aperture, which has improved transmission. Known metal foils with a thickness of less than 50 nm are unsuitable for electron microscopy because they provide poor images, frequently break (i.e., they are not freestanding or cannot be suspended on an EM grid such as a 50 μm grid without damage), and cannot adequately suspend the sample film.

[0027] The advantage of having an average linear intercept grain size of 50 nm or less is the absence of structural defects and reduced surface roughness, particularly at the edges of the apertures, allowing the metal foil to be successfully used in very high-resolution electron microscopy. Foils with these grain sizes are known, but all suffer from structural defects and inhomogeneities, making them unsuitable for electron microscopy, especially at high resolutions. Such known foils are typically formed as deposits on a support surface. In contrast, the metal foil of the present invention is robust enough to be self-supporting when suspended over openings (e.g., 50 μm grid squares in a TEM grid). Therefore, the foils of this disclosure are preferably unsupported, i.e., they are not disposed on a support layer. The specific grain size and absence of structural defects of the metal foil of the present invention allow for the formation of more rounded and smoother nanoscale apertures, providing stable support for suspended samples.

[0028] In some cases, the metal foil thickness is 49 nm or less, for example, 45 nm or less, 40 nm or less, 30 nm or less, 20 nm or less, 10 nm or less, or 5 nm or less. The metal foil thickness is preferably substantially constant throughout. Preferably, the foil thickness can fluctuate by a maximum of [missing value] throughout. or

[0029] In some cases, the average linear intercept grain size of the metal foil material can be 40 nm or smaller, such as 30 nm or smaller, 20 nm or smaller, 10 nm or smaller, or 5 nm or smaller. Lower grain sizes provide increased stability for thinner foils. For the best balance of advantages, an average linear intercept grain size of 10 nm or smaller is particularly preferred.

[0030] In some cases, the diameter of each hole is 750 nm or less, 700 nm or less, such as 600 nm or less, 500 nm or less, 400 nm or less, 350 nm or less, 330 nm or less, 300 nm or less, 250 nm or less, 200 nm or less, 180 nm or less, 150 nm or less, 100 nm or less, or 75 nm or less. In some cases, the diameter of each hole is selected from the range of 750 nm to 75 nm, 500 nm to 100 nm, 400 nm to 150 nm, 300 nm to 150 nm, or 250 nm to 150 nm. The holes are preferably substantially circular. The holes may all be substantially the same diameter or different diameters. The diameter of each hole is preferably substantially the same over the entire depth of each hole. Each hole passes completely through the metal foil. The spacing between the holes is preferably equal. The spacing between the holes is preferably equal to the diameter of at least one hole. The hole walls are preferably at a 90-degree angle to the foil surface, optionally with an accuracy of ±2 degrees or better. For any hole diameter, the hole depth is preferably 500 nm or greater. The sidewalls of the hole are preferably vertical or retrograde (tapered). Both of these preferences ensure that the holes formed in the foil are unlikely to be blocked by material subsequently deposited at the bottom / sidewalls of the holes during the process. The metal foil may include other secondary holes with diameters larger than the specified requirements above and / or that do not meet the above diameter-to-foil-thickness requirements. Because secondary holes do not meet the specified requirements, they are redundant. Alternatively, in some cases, the foil may only include holes that meet the specified requirements.

[0031] In some cases, the metal foil does not include any holes that do not meet the specified nanometer-scale diameter and / or diameter-to-thickness ratio requirements.

[0032] The advantage of nanoscale size is that the movement of particles within the pores is isotropic (the same in the support and in planes perpendicular to the support), spatially uncorrelated, and proportional to the root of the incident electron fluence, as in the case of purely random motion. In contrast, in known supports with larger pore diameters, at the start of irradiation (e.g., in the initial...) In the middle, there is a sudden, spatially correlated, undesirable displacement of the particles. This is followed by a decreasing correlated movement, which continues at a decreasing rate until the end of the exposure.

[0033] Another advantage is that the nanoscale pores provide plasmonic resonance in the visible light range, which makes the support appear yellow when reflected with white light but blue when transmitted. This property can be used to characterize the sample before electron imaging.

[0034] In some cases, the support has a maximum transmittance from 650 nm to 800 nm, such as 700 nm to 750 nm or 714 nm. The foil support may have a minimum transmittance from 500 nm to 600 nm, such as 625 nm to 675 nm or 645 nm.

[0035] In some cases, the purity of the metal foil material is 90% or higher, preferably 99% or higher, and even more preferably 99.999% or higher (i.e., the relevant metal material containing the stated percentage).

[0036] In some cases, the holes are arranged in a regular pattern on the metal foil, such as a hexagonal or square pattern. Preferably, the holes are arranged in a hexagonal pattern. The pattern is preferably regular. Hexagonal patterns provide a tighter packing and improve structural rigidity. Hexagonal patterns also allow for faster inspection of multiple holes by automated systems because the tighter packing of the holes in the membrane results in a shorter distance between the next hole, which speeds up the inspection of multiple holes.

[0037] In some cases, a metal foil is placed on an EM support grid. The grid provides additional structural support for the foil. In some cases, the foil and grid are integrally constructed. The foil and grid can be formed integrally. The foil and grid can have the same elemental composition throughout. The foil and grid can have different grain structures. The advantages provided by a grid and foil with the same elemental composition include increased stability during imaging because the two structures have the same coefficient of thermal expansion, and their mechanical behavior differs little or not at all with thermal changes (heating or cooling), resulting in little or no relative movement between the two structures. Although having the same elemental composition, the grain structure requirements for the grid material are not as stringent as for the metal foil, so the foil and grid can have different grain structures, such as grain size. The grid can be millimeter-sized, with such circular grids having a diameter of 5 mm, 4 mm, or most preferably 3 mm. The grid may include one or more support strips arranged to form a mesh, on which the foil can be suspended. In some cases, the mesh has an average aperture size in the micrometer range, such as about 300 μm, about 200 μm, about 100 μm, or about 50 μm. The apertures can be hexagonal or square. Preferably, the apertures are hexagonal. Preferably, the apertures are interlocked, i.e., if the apertures are square, they are arranged in a square array, and if they are hexagonal, they are arranged in a hexagonal array. Hexagonal apertures and arrays provide a tighter packing and improve structural rigidity. The aperture pattern can correspond to a foil aperture pattern.

[0038] In some cases, the grid is formed of a material selected from the same options listed herein for metal foils. In some cases, the grid comprises one or more metals selected from transition metals, aluminum, and beryllium, or alloys thereof. One or more transition metals may be selected from one or more of precious metals (ruthenium, rhodium, palladium, silver, osmium, iridium, platinum, gold), copper, molybdenum, titanium, nickel, chromium, tungsten, hafnium, and tantalum, or alloys thereof. Preferably, one or more transition metals are selected from the precious metals ruthenium, rhodium, palladium, silver, osmium, iridium, platinum, gold, or alloys thereof. Preferably, one or more transition metals are selected from gold, palladium, and platinum, or alloys thereof. Preferably, the grid comprises gold or an alloy thereof or is composed of gold or an alloy thereof. Preferably, the alloy is a binary alloy. Particularly preferred alloys include gold-silver alloys, gold-copper alloys, nickel-titanium alloys, gold-platinum alloys, and platinum-iridium alloys. The grid may not contain aluminum. The grid may not contain beryllium. The grid may not contain alloys.

[0039] In some cases, the grid comprises degenerate-doped silicon with a concentration of 10. 20 atoms / cm 3 Or higher dopant elements selected from boron, aluminum, boron and arsenic.

[0040] The hexagonal arrangement of the holes in both the foil and the mesh increases the usable area tenfold compared to a standard cryogenic EM grid. For example, it allows more than 800 images to be obtained from a single stage location and provides more than 5,000 individual holes in a single 25 μm wide hexagonal mesh.

[0041] In some cases, electron microscopy is transmission electron microscopy, preferably transmission electron cryomicroscopy.

[0042] A grid or mesh, which can serve as a support for the metal membrane, can in some cases be arranged along the edge of the support. The options for the material used for the support edge are the same as those for the grid described above. Preferably, the support edge is integral with the grid structure.

[0043] In the second aspect, the use of the support of the first aspect in electron microscopy, optionally in transmission electron microscopy, and preferably in transmission electron cryomicroscopy is provided.

[0044] In a third aspect, a method for manufacturing a metal foil for a support according to the first aspect is provided, the method comprising the steps of: depositing a metal layer onto a patterned substrate cooled to 200 K or lower to form a layer having a thickness of 50 nm or less and having one or more holes therethrough; removing the deposited metal layer; and forming the metal layer into a support for an electron microscopy sample, wherein the metal foil comprises: (a) one or more metals selected from transition metals, aluminum, and beryllium, or alloys thereof; or (b) degenerate-doped silicon, wherein the dopant element is selected from a concentration of 10 20 atoms / cm 3 Or higher levels of boron, aluminum, boron, and arsenic.

[0045] By cooling the substrate during the deposition step, a metallic layer can be produced on it that not only has a reduced grain size compared to deposition at room temperature, but also exhibits previously unknown superior uniformity and continuity at such a grain size, particularly for gold and other suitably described metals and materials. This is achieved because the lower temperature reduces the thermal energy of the atoms more quickly compared to when the surface is not cooled, thus reducing the movement of metal atoms on the deposition surface once they are deposited on the substrate. The atoms are rapidly fixed upon deposition on the substrate, resulting in less atomic movement and aggregation into smaller grains compared to when the surface is not cooled.

[0046] In some cases, the deposited foil is a metal foil as described herein.

[0047] Furthermore, for many small EM samples, the desired foil aperture size is a diameter smaller than the diffraction limit of known photolithography techniques currently used to fabricate sample supports, and for vapor-deposited metals, especially gold, it is less than approximately Thick foils are unstable due to their polycrystalline grain structure (e.g., they cannot be peeled off from the deposition substrate without significant damage). The method of the present invention provides a metal foil free from these defects.

[0048] In some cases, the patterned substrate is a silicon wafer, optionally with a diameter from 3 mm to 300 mm, for example, 100 mm. The silicon wafer can be a degenerate-doped silicon wafer with a resistivity < 0.02 Ohm·cm. Alternatively, a silicon wafer with a higher resistivity of 1 Ohm·cm to 30 Ohm·cm can be used. As described in Jefimovs 2017, the silicon wafer can be formed by Talbot displacement (phase interference) lithography. The template-substrate distance during phase interference lithography can be used to control the diameter of the holes in the silicon surface. A regular array of templates can set the spacing between the holes to be patterned in the substrate. The silicon substrate is patterned to form recesses therein corresponding to the holes in the desired metal foil.

[0049] In some cases, the metal foil can be integrally formed with the support arrangement of the grid strips, such as a mesh. In such cases, if it is desired to place the foil at a distance below the level of the top surface of the grid strips, a mask with the grid strip pattern is applied to a silicon template coated with photoresist to expose the grid strip areas only after development. These are then etched, for example, by reactive ion etching (RIE) to form trenches at the desired depth. This step may be necessary to ensure compatibility of the grid with current sample loading and imprinting equipment. If it is desired that the surface of the foil is flush with the top surface of the grid strips, this step is not required.

[0050] In some cases, a Bosch etching step is performed on the holes in the substrate. This controls their final depth and ensures that the hole walls are at a 90-degree angle to the substrate surface with an accuracy of 2 degrees or better.

[0051] In some cases, a cleaning step is performed on the patterned substrate before metal layer deposition. Cleaning can be performed by immersion in, for example, a piranha solution (3H₂SO₄:1H₂O₂, freshly mixed), oxygen plasma, or UV-ozone plasma. Cleaning helps remove contaminants that may lead to poor pore formation.

[0052] In some cases, a metal layer is deposited on a patterned substrate at a temperature of 150 K or lower, 125 K or lower, 100 K or lower, or 90 K or lower. The substrate temperature can be set from 84 K to 92 K. Preferably, to reduce the grain size of the metal foil and allow for the formation of more rounded, smoother holes through it, the substrate stage is maintained at 77 K (liquid nitrogen temperature) during evaporation. Higher deposition rates require cooling to lower temperatures. Deposition can be performed by electron beam or thermal evaporation. For example, assuming surface adsorption atomic diffusion has an activation energy of 0.5 eV, to... The deposition rate allows for the nucleation of crystals 10 nm or smaller at temperatures ranging from 200 K to below. The substrate with the deposited metal layer can be slowly heated to room temperature in a vacuum (approximately 50 K / hour or less) to prevent foil delamination.

[0053] Preferably, a lower optimal deposition temperature is desired for optimal growth of the metal crystals due to the high self-diffusion coefficient of the metallic material, such as gold. For the formation of a stable, continuous layer, the purity of the material to be deposited is preferably 90% or higher, more preferably 99% or higher, and even more preferably 99.999% or higher.

[0054] In some cases, the patterned substrate is provided with a first sacrificial layer applied to the patterned substrate on which a metal layer is deposited. Any layer that can be selectively etched for the associated metal foil layer can be used for this layer. The sacrificial layer can be a metal, such as copper (particularly preferred for gold foil). Copper is preferred as the sacrificial layer. The sacrificial layer can also be deposited on the substrate under the cooling conditions described above. The deposition conditions of the sacrificial layer are preferably the same as those of the metal foil layer. This is preferred because undesirable defects and roughness of the deposited sacrificial layer can be otherwise imparted to the sides of the metal foil layer formed thereon. The thickness of the sacrificial layer is preferably at least the same as the specified grain size. For example, a sacrificial layer with a thickness of at least 10 nm, or at least 25 nm, or at least 50 nm can be used. The maximum thickness of the sacrificial layer is preferably less than the radius of the hole in the foil.

[0055] In some cases, there are one or more steps involved in transferring the metal foil onto the EM grid. The foil can be transferred onto a commercial EM grid using a floating process. Alternatively, the grid can be fabricated directly on the substrate carrying the foil to provide an integrated foil and grid. The latter is the preferred option for mass production. It is preferable that the foil is integrally formed with at least the mesh of the grid strips and preferably the entire grid (the mesh of the grid strips and the thicker perimeter of the grid circle) because using the same metal for both the foil and the grid strips eliminates the difference in coefficients of thermal expansion and thus eliminates movement of the substrate during heating (e.g., beam heating when exposed to an electron beam).

[0056] In some cases, the support is based on the first aspect.

[0057] Support production is achieved by transferring metal foil to commercial grids.

[0058] To transfer metal foil to a commercial grid, steps may include peeling, cleaning, and placing the foil onto the grid. The foil may be coated with a 1 μm to 10 μm negative photoresist layer prior to peeling. The peeling step may include etching a sacrificial layer, such as copper, to release the foil from the substrate. The cleaning step may be performed by one or more HCl washes (e.g., washes with 20%, 2%, or 0.2% HCl, followed by at least three water rinses). The placement step may involve placing the foil onto a clean grid by arranging the grid on the bottom of a water-filled pan, where the foil floats and the water is slowly siphoned off. If a supporting photoresist layer is used, it can then be removed by washing the individual grids in a suitable solvent and treating with low-energy plasma.

[0059] Optionally, as described in Naydenova 2019, polymer-assisted graphene transfer can be performed after the foil is placed onto the grid.

[0060] Supports are produced by integrally forming a grid on a metal foil.

[0061] To produce a support with integrated metal foil and grid, a temporary photoresist is applied and excess foil between adjacent desired individual foils is etched away. A second temporary photoresist is applied so that grid strips and any optional additional features, such as alignment marks, reference points, labels, or unique identifiers, can be deposited by electroplating. The photoresist is applied using standard techniques, exposed under a mask, developed, and removed. After removing the second photoresist, the surface is cleaned with oxidizing plasma or UV-ozone. The supporting plastic layer is rotated across the grid. The support, now consisting of integrated foil and grid supported together on the same plastic layer, is then peeled from the substrate and cleaned, for example, by a series of washes with a 20% to 0.2% aqueous hydrochloric acid solution and water.

[0062] The electrodeposition step can form a deposited metal layer with a total thickness of 10 μm to 15 μm for the grid strips and edges. The metal layer can be deposited from an electrolyte solution, preferably a cyanide-free bath such as sulfite / thiosulfite. Such a solution typically has a concentration of the metal material to be deposited of 10 g / L to 15 g / L, and a current of 2 mA / cm². 2 Up to 10 mA / cm 2 It is used at an applied current density of 50°C to 60°C. Two of these parameters are varied to control residual stress in the electroplated metal layer. Under these conditions, for example, the electroplated gold has a Young's modulus of at least 35 GPa and a hardness of at least 40 Vickers.

[0063] The stripping step may include etching a sacrificial layer, such as copper, by chemical wet etching, typically in an etchant based on ferric chloride or ammonium persulfate. Stripping preferably occurs at room temperature for 20 minutes or less to prevent non-selective etching of the metal foil layer by the copper etchant. If etching is performed at higher temperatures, the time is approximately halved for every 10 degrees Celsius of heating. The grid can be released from the silicon template by etching silicon, preferably in a hot (80°C), stirred KOH solution (30%). Stripping occurs almost immediately upon immersion in the solution and is accompanied by the removal of the photoresist through the same solution. The individual grids released by this process can then be transferred to a KOH rinsing bath, followed by two deionized water baths, a piranha solution rinsing bath at room temperature (to remove any copper), and two additional deionized water baths.

[0064] After the washing step, the complete supports are sufficiently stable on the plastic layer for packaging and shipping. The plastic layer can be removed by dissolving it in a suitable solvent just before use of each complete support. Any remaining small amount of plastic can be removed by subsequently treating the cleaned grid with low-energy plasma. The grid can be placed on a suitable support, such as filter paper, and dried for later use.

[0065] Therefore, the requirements for a suitable plastic layer are (i) that it can be easily removed with solvents, (ii) that it is insoluble in water, HCl, copper etchants (ammonium persulfate or ferric chloride), and (iii) that it has sufficient flexibility and structural rigidity to peel off from the substrate and transfer to a washing bath. Examples of suitable plastics include positive or negative photoresists, polystyrene, and collodion.

[0066] Optionally, as described in Naydenova 2019, polymer-assisted graphene transfer can be performed immediately after the deposition of the metal foil to produce a graphene layer positioned between the foil and the grid strips. This is preferred in small-scale processes. Alternatively, it can be performed after the grid has been fully formed but still attached to the wafer. In the latter case, the plastic layer used to assist the graphene transfer can also be used as the plastic layer, or an additional plastic layer can be added as described above. If a large-scale process (e.g., wafer-scale) is used, graphene can preferably be transferred onto the grid after it has been released from the wafer. This can be achieved, for example, by transferring the grid from the wafer onto another temporary support structure, such as a suitable polymer that can later be dissolved in an organic solvent.

[0067] It has been determined that excellent support quality can be ensured if one or more of the following parameters are met: (a) the fraction of blocked / abnormal holes < 1% (caused by suboptimal cleanliness of the substrate prior to evaporation); (b) the roundness deviation of the holes < 10 nm (caused by insufficient grain size due to increased temperature and / or deposition rate during evaporation, or by partial etching of the foil during stripping); (c) the flatness of the hole edges < 10 nm (as above, also due to stencil wear); (d) the area of ​​grid strip defects < 1% (caused by defects in the mask); (e) the adhesion between the foil and the grid strip is sufficient to withstand the stress generated by rapid cooling from 277 K to 80 K (106 K / s or faster); and (f) the foil coverage > 99%.

[0068] These proposals also include EM supports, such as those formed by the methods described herein.

[0069] In a fourth aspect, an electron microscopy imaging method is provided, the method comprising the step of sequentially imaging a sample suspended in a hole in a support according to the first aspect, wherein each image covers at least a portion of the edge of the hole, and an electron beam covers the hole and the complete edge of the hole.

[0070] In some cases, at least a portion of the edge of the hole in each image is compared with other images to remove any relative offset between sequential images, and / or sequential images of the specimen in the hole are weighted to reduce the effect of specimen damage. Attached Figure Description

[0071] In order to understand the present invention, and in order to understand other aspects and features thereof, embodiments illustrating the principles of the invention will now be discussed in further detail with reference to the accompanying drawings, in which:

[0072] Figure 1 The movement of gold nanoparticles in glassy ice within a range of foil pore sizes is shown.

[0073] Figure 1 A shows a typical drift-corrected electron micrograph used for tracking gold particles in glassy water on an all-gold support; scale bar is 0.5 μm. The inset (20 nm × 20 nm) shows the gold nanoparticles at the start of irradiation and at... The overlay map of the initial and final positions after the injection volume.

[0074] Figure 1 B and Figure 1 C shows the root mean square displacement of 200 to 2000 particles from 10 to 50 films with different diameter apertures (UltrAuFoil R2 / 2-1.9μm, UltrAuFoil R1.2 / 1.3-1.2μm, UltrAuFoil R0.6 / 1-0.8μm, and custom grids with 0.3μm and 0.2μm apertures) plotted as a function of cumulative electron fluence for 0° tilt (B) and 30° tilt (C). Error bars show the standard error of the mean. All exposures were performed under the same irradiation conditions (300kV, 2.4μm beam diameter). Below. The ice thickness in all imaging holes is...

[0075] Figure 1 D shows that if the compressive stress (N) exceeds a critical value (N0) determined by the film's aspect ratio (2a / h), the ice film used in a cryogenic EM will bend during glass transition. Electron irradiation causes the film to move in response to the additional stress therein, as clearly seen from the movement of the relevant particles at the start of irradiation.

[0076] Figure 2 A shows a stress accumulation model in a thin film of amorphous ice during cryogenic immersion and its response to electron irradiation. The density of liquid amorphous water is plotted (star-shaped) as a function of temperature, guided by a solid line. During cryogenic immersion in liquid ethane, water typically cools rapidly from 277 K to 91 K (arrow at the bottom). The maximum specific volume change experienced by water below its homogeneous nucleation point is (ΔV / V). 最大 ≈5.5%. The film can only withstand a maximum of (ΔV / V) before it bends. 临界 Compression (critical stress accumulation range corresponds to a 300°A thick layer in a 1μm pore).

[0077] Figure 2 B shows the diffusivity of water molecules in liquid amorphous ice plotted (cross-shaped) as a function of temperature. The solid line represents the fitted values. The extrapolated diffusivity of amorphous ice at 84 K is very low, approximately [value missing]. The shaded area in the lower left represents the range of diffusivity of amorphous ice at temperatures from 0 K to 100 K, where it is stable indefinitely. During electron imaging with 300 keV, pseudo-diffusion movement of water molecules was observed. exist to At typical imaging throughput, this is equivalent to to (The shaded band between the top and the middle), and corresponds to an instantaneous local temperature of 147K.

[0078] Figure 3 A foil is shown as an all-gold sample support designed for motionless cryogenic EM imaging. Figure 3 A and 3B show optical micrographs of patterned gold foil (a hexagonal array of 200 nm diameter apertures with a 600 nm spacing) on ​​a 600-mesh gold grid under unpolarized white illumination (A) in reflected light and (B) in transmitted light. The scale and corresponding areas of (A) and (B) are identical. The blue color of the foil in transmitted light is due to enhanced red absorption caused by the periodic aperture pattern.

[0079] Figure 3 C shows a transmission electron micrograph of a single grid square on one of these grids. The 3mm grid contains approximately 800 of these hexagons, each containing more than 5,000 apertures in a regular pattern. Circles surround the more than 800 apertures, which can all be imaged at high magnification during high-speed data acquisition without moving the stage.

[0080] Figure 3 D shows a transmission electron micrograph of the porous gold foil. The arrows indicate the spacing of the regular hexagonal pattern.

[0081] Figure 3 E shows a transmission electron micrograph of a single pore in a nanocrystalline foil. The roundness of the 200 nm pore was improved by reducing the gold grain size to 10 nm.

[0082] Figure 3 F shows a low-dose transmission electron micrograph of a protein DPS (220 kDa) vitrified on the lattice of the present invention with 260 nm pores.

[0083] Figure 4 This demonstrates the use of a 260nm pore support in resolution and The structure of DPS determined by the injection volume.

[0084] Figure 4 A plot shows the mean square particle displacement (positive slope) of the ensemble of all DPS particles used in the reconstruction during irradiation, and a plot showing the linear fit between the relative B-factor and B-factor decay for each frame (negative slope), consistent with the expected slope for radiation-only damage. The mean square particle displacement is linearly related to the flux, which corresponds to... The effective diffusion constant is consistent with the pure diffusion shift.

[0085] Figure 4 B shows the selected side chains (His51, Glu82, Asp156) and water molecules reconstructed from each frame of DPS, demonstrating the progression of radiation damage. The residuals of the refined model are masked by atoms, and the contoured density map is shown as a mesh.

[0086] Figure 4 C shows the selected Fourier pixels plotted as a function of total volume. and The real part (triangle) and imaginary part (square) at resolution. The structure factor can be extrapolated to its value before irradiation begins, corresponding to the undamaged structure (fill symbol at 0 fluence).

[0087] Figure 5 The optical transmission spectra of the support of the present invention, continuous gold foil, commercial UltraAuFoil, and a bare grating for comparison are shown. The peak at 508 nm is characteristic of all thin gold films. Only the support of the present invention exhibits a characteristic minimum at approximately 645 nm and a maximum at 714 nm due to the diameter of its aperture being comparable to the wavelength of light. These are due to resonances corresponding to local surface plasmons around the aperture.

[0088] Figure 6 This demonstrates how the microscopic support of the present invention practically achieves the theoretical pseudo-diffusion limit compared to five known specimen support designs. Figure 6 A sample support for amorphous carbon on amorphous carbon in A. Figure 6 Suspended ice in B Figure 6 Graphene on carbon in C Figure 6 Gold in D and Figure 6 All graphene on E-gold exhibits RMS shift values ​​of ribosomes with Mw 2MDa, which are greater than Figure 6 The sample support of the present invention shown in F. Figure 6 F shows that it is actually the same as Figure 6 The RMS displacement value is the same as the theoretical pseudo-diffusion limit RMS displacement value shown in G.

[0089] Figure 7 The root mean square displacement of all tracked particles is shown. Figure 7 Figures A through 7J show the root-mean-square displacement of gold nanoparticles embedded in suspended ice films with different pore diameters as a function of cumulative fluence at tilt angles of 0° or 30°. Stage drift has been subtracted from these displacements. Error bars show the standard error of the mean. Dots indicate the displacement of a single particle (200 to 2,000 particles per figure). All exposures were performed under the same irradiation conditions (300 kV, 2.4 μm beam diameter). ( / second). The ice thickness in all imaging apertures is 300±50nm.

[0090] Figure 8 The image shows motion tracking on the same grid at different aperture sizes. The mean square displacements of particles smaller than 300 nm are imaged at 0° tilt (A) and 30° tilt (C), and the mean square displacements of particles in apertures with diameters ranging from 500 nm to 560 nm are imaged under the same conditions (B and D). The motion of particles in smaller apertures appears to be completely diffuse, while particles in larger apertures move as expected from the bending model.

[0091] Figure 9 The optimal aspect ratio for determining the stability of the suspended ice film is shown. The darkest shaded areas represent the range of combinations of pore diameter and ice thickness that are fully expected to be stable when vitrified in liquid ethane at approximately 90 K and imaged with electrons at liquid nitrogen temperatures. Combinations of pore diameter and ice thickness located in the white areas are expected to be unstable due to bending during vitrification. Dashed lines show the maximum stable pore diameter for a given ice thickness, while dotted lines represent more conservative estimates for the same threshold. These lines are merely indicative limits. The slope varies due to variations in ice thickness within the pores, pore shape, and the uncertainty of the Poisson's ratio for amorphous water. Different pore sizes and corresponding ice thicknesses (where gold nanoparticles are tracked in this work) are shown in black. Pore diameters and ice thicknesses from the DPS dataset are specifically marked.

[0092] Figure 10 The shape of submicron (nano) pores in nanocrystalline gold foil is shown. Transmission electron micrographs of typical pores in the gold foil, produced by evaporation onto a silicon template (210 nm pores) at ambient temperature (A) and at 85 K (B) achieved through liquid nitrogen cooling of the substrate, are shown. In both cases, gold is deposited at the same rate. Vapor deposition is then performed. Lowering the temperature reduces the gold grain size to one-tenth by decreasing the surface diffusivity of the deposited gold. This allows for the formation of more regular and rounded pores.

[0093] Figure 11A through 11E illustrate the improvements of the electron microscopy support of the present invention by detailing and comparing the defects in currently known supports.

[0094] Figure 12 Scanning electron micrographs of the HexAuFoil grid, which is entirely fabricated on a porous wafer and still attached to it, are shown. All micrographs were obtained using an Everhart-Thornley detector at an accelerating voltage of 30 kV and a 30° tilt.

[0095] Figure 12 A shows a complete HexAuFoil grid, 3 mm in diameter, separated from adjacent grids on a wafer. The darkest areas correspond to the exposed silicon surface of the stencil wafer. Arrow 1 points to one of the four reference marks in each of the four quadrants on the grid. The grid also has two eye-visible edge marks. The largest quadrant mark (arrow 2) has no foil, and this position is convenient for electron microscopy alignment and flux measurements. Arrow 3 points to the thin gold foil connecting strips between the grids that provide continuous electrical contact for electroplating. The dashed box indicates... Figure 12 Enlarged areas in B, 12C, and 12D (from top to bottom).

[0096] Figure 12 B shows that each grid contains a center mark. The text appears to be reflected in the design; when the grid is separated from the wafer and viewed from the flat foil side, it will be flipped to the correct orientation.

[0097] Figure 12 C shows each hexagon as 50 micrometers wide and containing 8,000 to 9,000 holes. In designs with alternative spacing, this size of hexagon can have 3,000 to 5,000 holes. For smaller hexagons, the number of holes per hexagon decreases proportionally to the opening area. The grid strips are formed by electroplating gold and are 10 micrometers wide and 10 micrometers thick in this example. The preferred thickness is 5 to 20 micrometers. The aspect ratio (thickness / width) of the strips is preferably in the range of 0.25 to 4, and in most cases 0.5 to 2, equal to 1 in this example.

[0098] Figure 12 D shows that each grid has a clearly defined edge mark, which is also visible to the naked eye (requiring a size of at least 0.2 mm). The radial direction from the grid center toward the edge mark is indicated by a line passing through the middle of the hexagon. This line is visible in an electron microscope and can be used, along with other alignment features, for example, to map the orientation of the grid in a microscope relative to its orientation during sample preparation.

[0099] Figure 13 HexAuFoil grids with aperture diameters ranging from 200 nm to 300 nm are shown. Figure 13 A and Figure 13 B shows two scanning electron micrographs of HexAuFoil gold foil still attached to the template silicon porous wafer via a sacrificial copper underlayer. Both micrographs were obtained using an Everhart-Thornley detector at an accelerating voltage of 30 kV and a 0° tilt. The scale is set by the center-to-center aperture spacing (600 nm for both). Figure 13 A and Figure 13 The only difference in the foil in B is the diameter of the template hole; each, for Figure 13 A, the template aperture diameter is 300nm, and for Figure 13 B, the template aperture diameter is 200 nm. Gold foil disks can be seen at the bottom of each aperture in the silicon wafer, where the shading angle depends on the viewing angle from the gold source towards a given point on the wafer during electron beam evaporation of the foil. If the aperture is not deep enough, these disks can remain attached to the foil and block the aperture when the foil is released from the wafer. For apertures from 200 nm to 300 nm and... Thick copper and gold foil, at a depth of 500nm, is sufficient to avoid this situation.

[0100] Figure 14 The HexAuFoil grid released from post-wafer manufacturing is shown.

[0101] Figure 14 Image A shows a scanning electron micrograph of the strip side of the grid after the copper adhesive layer was released and removed from the wafer (45° tilt, using an Everhart-Thornley detector at an accelerating voltage of 2 kV). The grid was clamped in a standard clamp / clip holder for transmission electron microscopy.

[0102] Figure 14 B shows the flat foil side of the grid (i.e., on the grid relative to its position). Figure 14 A scanning electron micrograph of one of the hexagons on the same grid (45° tilt, using an Everhart-Thornley detector at an accelerating voltage of 30 kV) obtained after orientation reversal in A. This is the side of the grid initially covered by a sacrificial copper layer in contact with the silicon template. The porous foil spans each grid hexagon and remains intact.

[0103] Figure 14 C shows a scanning electron micrograph of the porous gold foil (45° tilt, using an Everhart-Thornley detector at an accelerating voltage of 30 kV), revealing the edge flatness of each pore and the surface flatness of the foil. These properties contribute to the formation of a thin, flat ice layer when the grid is used for cryogenic EM sample preparation.

[0104] Figure 14Image D shows a transmission electron micrograph of suspended gold foil on a grating after being removed from a wafer. This suspended gold foil can be used as a sample support for transmission electron microscopy. The spacing between the apertures is 600 nm. The dashed box delineates... Figure 14 The magnified area in E.

[0105] Figure 14 E shows a transmission electron micrograph of a hole in a gold foil with a freestanding HexAuFoil grid. As shown, the hole diameter is 300 nm. The edge roughness is limited by the grain size of the gold foil, which in this case is about 20 nm for gold deposited at a substrate temperature of 85 to 90 Kelvin. The dashed black circle is precisely circular and used for comparison with the edge of the hole.

[0106] Figure 14 F shows statistical data on the in-plane movement of gold nanoparticles in HexAuFoil gratings produced by the wafer-scale method (right), indicating that these gratings perform comparably to HexAuFoil gratings produced by the small-scale method in a previous publication (Naydenova, Jia & Russo 2020) (left). Detailed Implementation

[0107] The features disclosed in the foregoing description, the appended claims, or the drawings, expressed in their specific form or according to the method or process for performing the disclosed function or for obtaining the disclosed result, may, as appropriate, be used alone or in any combination of such features to implement the invention in its different forms.

[0108] Although the invention has been described in conjunction with the exemplary embodiments described above, many equivalent modifications and variations will become apparent to those skilled in the art when considering this disclosure. Therefore, the exemplary embodiments of the invention set forth above are to be considered illustrative rather than restrictive. Various changes may be made to the described embodiments without departing from the scope of the invention.

[0109] To avoid any ambiguity, any theoretical explanations provided herein are offered for the purpose of improving the reader's understanding. The inventor is not bound by any of these theoretical explanations.

[0110] Any chapter headings used in this document are for organizational purposes only and should not be construed as limiting the subject matter described.

[0111] Throughout this specification (including the appended claims), unless the context otherwise requires, the words “having,” “comprising,” and “including,” and variations thereof, shall be construed as implying the inclusion of the indicated integer or step or group of integers or steps, but not excluding any other integer or step or group of integers or steps.

[0112] It is important to note that, unless the context explicitly indicates otherwise, the singular forms “a,” “an,” and “the” used in the specification and appended claims include plural references. A range may be expressed herein as from “about” one particular value and / or to “about” another particular value. When such a range is expressed, another embodiment includes from one particular value and / or to another particular value. Similarly, when a value is expressed as an approximation using the preceding “about,” it will be understood that the particular value forms another embodiment. The term “about” in relation to numerical values ​​is optional and signifies, for example, + / - 10%.

[0113] As used herein, the terms "preferred" and "ideally" refer to embodiments of the invention that provide certain benefits in some circumstances. However, it should be understood that other embodiments may also be preferred in the same or different circumstances. Therefore, the description of one or more preferred embodiments does not imply that other embodiments are useless, nor is it intended to exclude other embodiments from the scope of this disclosure or the claims.

[0114] As used herein, the term "metallic" refers to materials or components that exhibit metallic properties (e.g., foils). In particular, they exhibit high electrical and thermal conductivity. In many cases, metallic materials have electrical conductivity greater than 10. 4 S / m.

[0115] Electron microscopy support

[0116] An electron microscopy support is a device that allows samples to be examined by electron microscopy to be transported in and out of an electron microscope. The support is provided with a degree of mechanical strength by its internal outer walls or edges, typically arranged as a grid of components (e.g., grid strips). The sample to be examined is mounted on the support within the area defined by the grid strips. In cryogenic EM, the sample itself is suspended in a membrane (e.g., a glassy ice film) suspended in the pores or holes of a foil suspended between the grid strips. The foil is often also referred to as a support membrane.

[0117] The foil portion of the support typically has a mesh or "porous membrane" structure. These foils are often described in the art using two numbers, such as "2 / 1"—this means a foil with two micrometer-sized pores at a one-micrometer pitch. Similarly, a foil designated as 2 / 4 would have two micrometer-sized pores or holes at a four-micrometer pitch, and so on. The term "support" includes both cases where the foil is provided with a grid and cases where it is not.

[0118] Example 1 - High-resolution cryogenic EM structure determination of DNA protection during starvation protein (DPS)

[0119] To demonstrate the applicability of a non-moving sample support for high-resolution cryogenic EM, the structure protecting 220 kDa DNA during starvation protein (DPS) was determined. The DPS was placed in a support with 260 nm pores. Freezing was performed on a thick gold foil grid. The average resolution of the initial reconstruction, achieved through automated data collection over approximately 9 hours using a modern 300 keV microscope, was easily achieved. And in The total particle displacement under irradiation is RMS. The absence of bending also ensures no significant particle rotation during imaging. Compared to all previous single-particle cryo-EM datasets to date, the reconstructed image from each frame shows the first frame ( The 3MGy (or 3MGy) contains the most structural information, and the quality (B-factor) of consecutive frames decreases linearly with dose / flux. From radiation damage studies in X-ray and electron crystallography, a linear decrease in the B-factor with dose is expected; however, due to the shift at the start of irradiation, a linear decrease in the B-factor with dose has never been previously observed for cryogenic EM of a single particle.

[0120] Example 2 - Characterization of Gold Foil

[0121] The average linear intercept grain size of some gold foils manufactured as described in this article was measured by TEM and found to be... This is about one-twentieth the grain size of gold foil manufactured under similar conditions but at room temperature. The smaller grain size allows for both thinner foil and smoother hole edges. The typical edge roughness (deviation from a circular shape) of a 200nm to 300nm hole is less than 10nm.

[0122] Comparative example - the previous foil is not suitable for the purpose.

[0123] The following examples illustrate the improvements of the electron microscopy support of the present invention by detailing and comparing the shortcomings of currently known supports.

[0124] Defect Type 1: Irregular holes caused by increased grain size due to increased evaporation rate.

[0125] Will Figure 11 The gold film shown in A is The copper layer (not shown) is deposited at a rate of [missing information - likely a specific velocity or temperature] onto a patterned substrate held at approximately 90 K. Evaporation. These evaporation rates result in deformed pores due to the increased grain size. The pore diameter varies between 50 nm and 250 nm. Figure 11 Compared to the foil in D, it is produced at the same temperature but at a lower rate (for both copper and gold). The foil is produced by vapor deposition onto the same template and has the same thickness. In this foil, the typical deviation of the hole from the roundness is 10 nm or less.

[0126] Defect Type 2: Irregular holes caused by increased grain size due to increased vapor deposition temperature are shown in the figure. Figure 10 In A.

[0127] Defect Type 3: Aberrations caused by over-etching

[0128] Figure 11 The gold foil shown in B is from Figure 11 E's gold foil is deposited onto the same substrate using the same method. The release of this film (etching the sacrificial Cu layer in ferric chloride) is compared to... Figure 11 The release of the film in E is half as slow (30 minutes vs. 15 minutes). This results in irregular enlargement of the pores (approximately 50 nm) due to gold etching via ferric chloride. The distance between the pores (spacing) is 600 nm.

[0129] Defect type 4: Porosity

[0130] Figure 11 The gold foil shown in C is manufactured using the method described in Russo 2014, where gold vapor deposition is performed at room temperature. The foil thickness is... And the diameter of the pores is 2 μm. This is thicker than the foil of this invention. Due to the relatively large grain size of approximately 200 nm, the foil remains porous and unstable at this thickness. This is demonstrated using the paper Russo 2014, which shows that even... Thick foils also become unstable due to this porosity and the discontinuous nature of the metal foil. Typical pore sizes are 200 nm long × 10 nm wide and 30 μm / m. 2 Up to 40 / μm 2 .

[0131] Gold foil produced by sputtering as described by Janbroers et al. (2009) also possesses this porosity, except that it is not made of pure gold. Figure 1 C and Figure 5 The central hole is clearly visible. This contrasts with the foil of the present invention, which does not have such a hole.

[0132] Although the data presented in this article pertain to gold, it is expected that similar data will be available in materials with similar structures and electrical properties, such as transition metals, aluminum, beryllium, and those with a concentration of 10. 20 atoms / cm 3 Similar improvements can be seen in degenerate-doped silicon with higher concentrations of a second element selected from boron, aluminum, phosphorus, and arsenic.

[0133] References

[0134] 1. Ermantraut, E., Wohlfart, K. & Tichelaar, W. Perforated supportfoils with pre-defined hole size, shape and arrangement. Ultramicroscopy 74, 75-81 (1998).

[0135] 2. Janbroers, S., de Kruijff, TR, Xu, Q., Kooyman, PJ & Zandbergen, HWPreparation of carbon-free TEM microgrids by metalsputtering. Ultramicroscopy 109, 1105-1109 (2009).

[0136] 3. Russo, CJ & Passmore, LAUltrastable gold substrates for electroncryomicroscopy. Science 346, 1377-1380 (2014).

[0137] 4. Russo, CJ & Passmore, LA Ultrastable gold substrates: Properties of fasupport for high-resolution electron cryomicroscopy of biological specimens. Journal of Structural Biology 193, 33-44 (2016).

[0138] 5.Grant-Jacob,J.A.et al.Design and fabrication of a 3D-structuredgold film with nanopors for local electric field enhancement in thepore.NaRotechnology 27,65302(2015).

[0139] 6.Jia,P.etal.Large-area freestanding gold nanomembranes withnaRoholes.Materials Horizons 6,1005-1012(2019).

[0140] 7.Naydenova,K.,Peet,M.J.&Russo,C.J.Multifunctional graphene supportsfor electron cryomicroscopy.Proceedings of the National Academy of Sciences201904766(2019)doi:10.1073 / pnas.1904766116.

Claims

1. A support for an electron microscopy sample, the support comprising a metal foil having one or more holes therethrough, wherein the metal foil has a thickness of less than 50 nm and an average linear intercept grain size of 50 nm or less, wherein the ratio of the diameter of each hole to the thickness of the metal foil is 15:1 or less, and wherein the metal foil is composed of: (a) One or more metals selected from transition metals, aluminum and beryllium, or alloys thereof; Or (b) degenerate-doped silicon, wherein the dopant element is selected from a concentration of 10 20 atoms / cm 3 Or higher levels of boron, aluminum, boron, and arsenic.

2. The support according to claim 1, wherein the edge roughness of each hole is 20 nm or less, based on the measured root mean square deviation relative to the expected theoretical hole edge profile.

3. The support according to claim 1 or claim 2, wherein the diameter of each hole is 750 nm or less.

4. The support according to claim 1 or claim 2, wherein the maximum optical wavelength transmittance of the support is between 650 nm and 800 nm.

5. The support according to claim 1 or claim 2, wherein the holes are arranged in a hexagonal array or a square pattern array.

6. The support according to claim 1 or claim 2, wherein the metal foil is suspended across a hole in an electron micrograph.

7. The support according to claim 6, wherein the metal foil and the grid are integrally formed.

8. The support according to claim 6, wherein the grid comprises a mesh with an average aperture size in the micrometer range, and the mesh apertures are fitted hexagons or fitted squares.

9. The support according to claim 1 or claim 2, wherein the metal foil is composed of one or more of gold, palladium and platinum, or an alloy thereof.

10. The support according to claim 9, wherein the metal foil is composed of gold or an alloy thereof.

11. The support according to claim 1 or claim 2, wherein the support is composed of one or more of gold, palladium and platinum, or an alloy thereof.

12. The support according to claim 11, wherein the support is composed of gold or an alloy thereof.

13. Use of the support according to any one of claims 1 to 12 in transmission electron microscopy.

14. A method for manufacturing a metal foil for a support according to any one of claims 1 to 12, the method comprising the steps of: Deposit a metal layer on a patterned substrate cooled to 200 K or lower to form a layer with a thickness of 50 nm or less and having one or more pores passing through it; Remove the deposited metal layer; and form the metal layer as a support for an electron microscopy sample, wherein the metal foil consists of: (a) one or more metals selected from transition metals, aluminum and beryllium, or alloys thereof; Or (b) degenerate-doped silicon, wherein the dopant element is selected from a concentration of 10 20 atoms / cm 3 Or higher levels of boron, aluminum, boron, and arsenic.

15. A metal foil for a support formed by the method according to claim 14.

16. An electron microscopy imaging method comprising the step of sequentially imaging a sample suspended in a hole in a support according to any one of claims 1 to 12, wherein each image covers at least a portion of the edge of the hole and an electron beam covers the hole and the complete edge of the hole.

17. The electron microscopy imaging method of claim 16, wherein at least a portion of the edge of the hole in each image is compared with other images to eliminate any relative offset between sequential images and / or wherein sequential images of the specimen in the hole are weighted to reduce the effect of specimen damage.

Citation Information

Patent Citations

  • Sample support structure and methods

    US20100143198A1